2017
DOI: 10.1038/cmi.2017.4
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of inflammation and tumorigenesis by the TIPE family of phospholipid transfer proteins

Abstract: The TIPE (tumor necrosis factor-α-induced protein 8-like) family are newly described regulators of immunity and tumorigenesis consisting of four highly homologous mammalian proteins: TNFAIP8 (tumor necrosis factor-α-induced protein 8), TIPE1 (TNFAIP8-like 1, or TNFAIP8L1), TIPE2 (TNFAIP8L2) and TIPE3 (TNFAIP8L3). They are the only known transfer proteins of the lipid secondary messengers PIP2 (phosphatidylinositol 4,5-bisphosphate) and PIP3 (phosphatidylinositol 3,4,5-trisphosphate). Cell-surface receptors, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 79 publications
(115 reference statements)
3
54
0
Order By: Relevance
“…TNFAIP8 is the principal member of this family that is induced by TNF-α in response to environmental stress (11). It has previously been identified that TNFAIP8 is overexpressed in a wide range of different cancer types, and additional previous studies have demonstrated that it serves as an oncoprotein, as it induces the development and progression of tumors, and enhances cancer cell survival, proliferation and metastasis (12,23,24). However, little is known regarding the biological and pathological functions of TNFAIP8 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNFAIP8 is the principal member of this family that is induced by TNF-α in response to environmental stress (11). It has previously been identified that TNFAIP8 is overexpressed in a wide range of different cancer types, and additional previous studies have demonstrated that it serves as an oncoprotein, as it induces the development and progression of tumors, and enhances cancer cell survival, proliferation and metastasis (12,23,24). However, little is known regarding the biological and pathological functions of TNFAIP8 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…as an anti-apoptotic and pro-oncogenic signaling molecule (9)(10)(11)(12). A previous study suggested that tumor necrosis factor α (TNF-α) stimulation and the activation of the nuclear factor-κB pathway may upregulate the mRNA expression levels of TNFAIP8 in head and neck squamous cell carcinoma cell lines (13).…”
Section: Tnfaip8 Promotes Cisplatin Resistance In Cervical Carcinoma mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, murine macrophage Raw264.7 and T lymphocyte EL4 cells were transfected with Migr1 control and a TIPE overexpression vector due to their abilities for suitable DNA transfection (18). In despite of the fact that TIPE is a newly described regulator of immunity and tumorigenesis and is the only known transfer protein of the lipid second messengers (22,23), the exact mechanism of TIPE-mediated pro-survival effects remain uncertain. In the present study, we observed that TIPE inhibited cell apoptosis and promoted tumor formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The TIPE (tumor necrosis factor-α induced protein 8) family are newly described regulators of immunity and tumorigenesis and are composed of four highly homologous proteins: TNFAIP8 (TIPE), TNFAIP8L1 (TIPE1), TNFAIP8L2 (TIPE2) and TNFAIP8L3 (TIPE3) [6,7]. TNFAIP8, also known as SCC-S2, GG2-1, NDED, and MDC-3.13, was the first described member of the TIPE family.…”
Section: Ivyspringmentioning
confidence: 99%